A Bildungsroman never published: “Il compratore di anime morte” - Samuele Bonciani (Finzioni, 2022)
This essay presents an analysis of Stefano D’Arrigo’s unpublished typewritten novel Il compratore di anime morte aimed at demonstrating that it is not only a reduced rewriting of Dead souls, but a work disposed of its own features, especially in the ending, which differs from that of its Russian model. The attempt is to prove that the Compratore presents the typical Bildungsromans’ ending, a fact that could have been perceived out of date by D’Arrigo to the point of prompting him to give up publishing it.